Phytochemical Analysis of Aqueous and Alcohlic Extract Of Some Medicinal Plants - Suresh G. Jadhao, Prashant Thakare, Sonali D. Borkar, Alka R. Sawarkar, (International Journal of Scientific Research and Management (IJSRM), 2016)
Medicinal plants have bioactive compounds which are used for curing of various human diseases as well as animal diseases and also play an important role in healing. Phytochemicals have two categories i.e. primary and secondary constituents. Primary constituents have chlorophyll, proteins, sugar and amino acids. Secondary constituents contain terpenoids and alkaloids. Medicinal Plants have antifungal, antibacterial and anti-inflammatory activities. The present study involves three different medicinal plants Moringa oleifera, Dalbergia sissoo and Saraca indica. The leaves of the selected medicinal plants were washed, air dried and then powdered. The aqueous and alcoholic extract of leaf samples were used for the phytochemical analysis to find out the phytochemical constituents in the plant. The aim of the present study was to carried out the phytochemical analysis of aqueous and alcoholic extract of Moringa oleifera, Dalbergia sissoo and Saraca indica. Moringa oleifera is one of the species of family Moringaceae. Moringa oleifera is commonly known as “Drumstick”. Ashoka is the most ancient tree of India, known as a Saraca asoca (Roxb.), De.wild or Saraca indica belonging to family Caesalpinaceae. Dalbergia sissoo belonging to family Fabaceae and commonly known as Shisham or Sisam. The present study reveals the medicinal values of Moringa oleifera, Dalbergia sissoo, Saraca indica after reviewing their Phytotochemical analysis.